Keyimages ontologized for the Cultural Masses - MAC an AIRCHINNIGH, MICHEAL (University of Sofia, 2011)
Humans name things. Naming is essential for pointing to recognizable images, sounds, and emotions. In every culture throughout history certain stereotypical images have emerged to indicate grounded truths for the people. Today, where images are ubiquitous in their billions, available for use at a price, it becomes important to provide a balancing counterpart of high quality, royalty free images, under an appropriate creative commons licence. In addition to the usual folksonomical tagging it is recommended to have, in addition, a formal support vocabulary for which there is an appropriate formal reasoning system. In this paper we continue the pragmatic exposition of the CIDOC Conceptual Reference Model, supported by the Erlangen OWL encoding, and exercised through the Prote?ge? editor. Examples of keyimages are drawn from Television programs, online Art Galleries, and ordinary printed photographs. Vocabulary data are normally provided in both Bulgarian and English. Data in other languages, such as Gaeilge, French, German and Russian, are entered as needed.
PUBLISHED
Keywords: Computer science; ambiguity; digital re-discovery of culture; folksonomy; keyimage; ontology